COVID-19 Pandemic and Mental Health Issues - Bhattarai, Aabishkar; Karki, Bijaya (Journal of Lumbini Medical College, 2020)
In January 2020, the World Health Organization (WHO) declared the outbreak of novel coronavirus disease (COVID-19), a Public Health Emergency of international concern. WHO stated that there is a high risk of COVID-19 spreading to countries around the world. In March 2020, WHO declared COVID-19 as a global pandemic. From December 2019 till today (18 June 2020) the total cases have approached to 8,242,999 with the death of 445,535 and the incidence is increasing day by day. From the first case seen in Wuhan, China the virus has been rapidly spreading to most of the countries of Asia, Europe and America with almost all the world population affected directly by the disease or its consequences. The physical, social, economic, psychological, and mental wellbeing of the world population have been affected with this pandemic in its peak. To control this pandemic, most of the resources and manpower are dedicated to the patients with COVID-19 and the health care workers and volunteers who work in frontline. Governments have implemented lockdown modalities with a hope to reduce the burden of transmission in their countries, which has surpassed more than 2-3 months in most countries. The effect of pandemic, lockdown and social isolation approach have risen concern regarding their consequences to the mental health of the general population.